Clinical Consensus Statement: Vaginal Energy-Based Devices. Issue 1 (January 2023) - Alshiek, Jonia; Garcia, Bobby; Minassian, Vatche; Iglesia, Cheryl B.; Clark, Amanda; Sokol, Eric R.; Murphy, Miles; Malik, Shazia A.; Kimble, Alexis; Shobeiri, S. Abbas
Abstract : (Abstracted from Urogynecology 2022;28:633–648) The US Food and Drug Administration (FDA) announced a July 2018 public warning for using energy-based devices (EBDs) for performing vaginal cosmetic procedures or vaginal rejuvenation, based on both the imprecision of the term "vaginal rejuvenation" and the lack of FDA approval of the use of any devices such as lasers for any specific gynecologic indication. Some health care providers subspecializing in female reconstructive surgery and pelvic medicine deliver patient services via the EBDs discussed in the FDA Safety Communication.